Alternative Futures for Library History - Rose, Jonathan (Information & culture, 2019)
In response to a recent article by Donald Davis and John Aho, “Whither Library History?,” Jonathan Rose discusses six possible alternatives for the future of library history. Library historians can either continue to produce a traditional kind of library history or reframe their subject as a subfield of information science, mainstream history, or the history of the book. They can also adopt the models of such critical theorists as Antonio Gramsci and Michel Foucault. Rose argues for a sixth option: to make library history a part of the new academic discipline of book studies.